Analisis germane load dilihat dari minat belajar dan gaya belajar matematika siswa SMP di kelas virtual - Erwin Yuniyanto; Aan Hendrayana; Cecep Anwar Hadi Firdos Santosa (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
The purpose of this study was to describe the Germane load judging from learning interest and learning styles of Senior High School in Virtual Class. This research will be implemented at SMPN 29 Tangerang City with a population of all class VIII students and the sample in this study is one class from class VIII in the 2020/2021 school year. The material is a two-variable system of linear equations. This study uses a qualitative method. Sampling of research subjects was done by purposive sampling. The data collection techniques are test techniques and non-test techniques. This research will use written tests, questionnaires, interviews, observations, documentation, and FGD (Forum Group Discussion). From 30 students, 12 students were selected as research subjects. The results of the analysis of the ability of Germane Load on the research subjects concluded that the ability of Germane Load depends very much on their learning interests and learning styles. The learning interests and learning styles of each student are indeed different, depending on several factors and also from the responses and views of each of these students in learning mathematics both in virtual classes, then from the material learning, also the conditions of their learning environments.